Impact of movement control Order (MCO) on primary Percutaneous Coronary Intervention (PCI) at a tertiary Centre in Malaysia. - Nokarajoo, Linggesh; Mohd Firdaus, Mohd Al-Baqlish; Kohgulakuhan, Yogalingam; Hadi, Mohd Firdaus; Sukahri, Samshol; Hamzah, Syuhada; Mohd Said, Mohd Ridzuan; Wan Ahmad, Wan Azman (2021)
Introduction: The pandemic of Covid-19 infection has affected all primary health services including subspecialty services in healthcare facilities across Malaysia. The cardiology service worldwide especially the primary percutaneous coronary angioplasty for ST- elevation myocardial infarction (STEMI) was also affected due to the current pandemic. In this study, we would like to examine the effect of the covid-19 pandemic to a leading cardiology service of a tertiary centre in Malaysia. Methods: The study evaluated retrospective data from the Invasive Cardiovascular Laboratory (ICL), National Cardiovascular Database (NCVD) Registry, and medical records of University Malaya Medical Centre (UMMC). We used quantitative methods to gather and compare data on the total catheterisation procedures performed in UMMC, total patients whom presented with acute coronary syndrome (ACS) and patients whom underwent Primary Percutaneous Coronary Intervention (PCI) prior to the covid-19 movement control order (MCO), during the MCO and post MCO during the Recovery Movement Control Oder (RMCO). Data was analysed using thematic analysis obtained from seven cardiology consultants of UMMC on factors affecting the cardiology services during the pandemic and alternative measures in the event of another healthcare system crisis. Results: The total number of angiograms and angioplasty performed in UMMC reduced by 50% during the MCO period and incidence of cases of ACS also reduced by 45.4% during the MCO period. Reduction of 68% for number of primary PCIs were reported during the MCO period. However, we found that the average door- to-balloon time for primary PCIs during period of MCO and prior to MCO were similar. Thematic analysis suggested a comprehensive protocol or “pandemic play book” and crisis training should be available to government-based healthcare services. Conclusion: This unprecedented global crisis has undoubtedly impacted on all walks of life. We hope that this study has shed light on the challenges and effects of the covid-19 pandemic on a cardiology service in a tertiarycentre in Malaysia and what preventive steps can be put in place to be prepared for such healthcare crisis.